Development and Optimization of Fluvastatin Sodium Loaded Biodegradable Microspheres (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Fluvastatin sodium is a hypolipidemic agent that reduces cholesterol synthesis by inhibiting HMG-CoA reductase. The drug has a comparatively short biological half-life (1.2 hours) and low bioavailability (24–29%), making it an appropriate candidate for a sustained-release drug delivery system. This study aimed to formulate biodegradable microspheres of fluvastatin sodium by optimization through an experimental design approach. Microspheres containing fluvastatin sodium were prepared by o/w emulsification solvent evaporation method using poly (lactic-co-glycolic acid) (PLGA 50:50) as a biodegradable polymer. 32 full factorial design was applied to study the effect of drug to polymer ratio and stirring speed on dependent variables, i.e. particle size, entrapment efficiency, Q1h, t80%. Prepared formulations were subjected to evaluate physicochemical properties and release characteristics. DSC and FTIR proved no interaction between the drug and excipients. Microspheres possessed size in the range of 193 to 344 μm and entrapment efficiency varied from 63.1 to 85.6%. Formulations showed drug release up to 23% within 1-hour. while t80% was found in between 3–9 hours. Regression analysis and ANOVA results suggested a significant effect (p<0.05) of variables on responses. The results of the present study suggested that biodegradable microspheres of fluvastatin sodium prepared using poly (lactic-co-glycolic acid) can be a promising alternative for conventional delivery and suitable for sustained drug release.